2017
DOI: 10.1007/s11356-016-8332-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wastewater effluent derived ligands on copper and zinc complexation

Abstract: The shift toward bioavailability-based standards for metals such as copper and zinc not only improves the ecological relevance of the standard but also introduces significant complexity into assessing compliance. This study examined differences in the copper and zinc complexation characteristics of effluents from a range of different sewage treatment works and in relation to so-called ‘natural’ samples. This information is essential to determine whether the inclusion of effluent-specific complexation character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Some components, such as EDTA and other "EDTA-like" substances, are known to bind metal ions, which may influence metal bioavailability in an unpredictable manner (Knepper et al, 2005;Peters et al, 2014;Constantino et al, 2017). Recent data from 162 wastewater treatment effluents in the United Kingdom reveal the median EDTA concentration of 128 mg/L (0.44 mM), which is 5.3 and 22.9 times greater than those of dissolved zinc and copper, respectively (Constantino et al, 2017). We also confirmed that EDTA-bound copper affects the bioavailability of copper in aqueous solution (Figures 6C,D).…”
Section: Discussionmentioning
confidence: 99%
“…Some components, such as EDTA and other "EDTA-like" substances, are known to bind metal ions, which may influence metal bioavailability in an unpredictable manner (Knepper et al, 2005;Peters et al, 2014;Constantino et al, 2017). Recent data from 162 wastewater treatment effluents in the United Kingdom reveal the median EDTA concentration of 128 mg/L (0.44 mM), which is 5.3 and 22.9 times greater than those of dissolved zinc and copper, respectively (Constantino et al, 2017). We also confirmed that EDTA-bound copper affects the bioavailability of copper in aqueous solution (Figures 6C,D).…”
Section: Discussionmentioning
confidence: 99%
“…The different water types (Nitrate-phosphate type for both Kaleb and Ibrahim versus sulfate type for Beirut river course) do not affect the behavior of total Cu in water. It is well known that Cu undergoes a phenomenon of solvation in water to form copper hydrate, which is a stable form in addition to the other forms of copper chemical species at pH 7 due to inorganic complexation (mainly copper carbonate(Byrne and Miller, 1985;Conry, 2005;Constantino et al, 2017; …”
mentioning
confidence: 99%